Välfärd hos växande nötkreatur – finns den? - Wulf, Rebecka (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
During an investigation of animal welfare in animal production, the focus has for a long time been focused on the absence of stress, suffering and injuries, and positive emotions have not been prioritized. However, in recent years that has been drastically changed. The public interest have increased for buying animal products from animals that have had a decent life, which have led to that play, exploratory behavior and other positive behaviours has come to play a significant role in welfare assessment. The welfare of cattle is difficult to assess since there is currently no ancestors to study, it is thus difficult to determine which behaviors can be regarded as natural and thus positively related, acordingly the welfare of cattle have been forgotten and research on positive emotions of cattle have not been prioritized.